Analysis of longitudinal plantar arch in female artistic gymnasts - Kalichová, M.; Hedbavny, P.; Dolana, P. (Science of Gymnastics Journal, 2018)
The aim of the study was to use plantographic measurements to analyse the condition of longitudinal plantar arch in a group of female artistic gymnasts and to find out to which characteristics of gymnasts they are related. The study group included 52 artistic gymnasts at a high performance level. Using static measurement on an Emed platform plantographs were acquired which were then evaluated by the Chippaux-Šmiøák method, the results were then scaled according to Klementa norms. In 89 measured feet out of 104 a high longitudinal foot arch was detected. Out of these 5 were slightly high, 14 were medium high and 70 were very high. The remaining 15 gymnasts had a normal longitudinal foot arch. By calculating the Pearson correlation coefficient we found out that with the duration of gymnastic practice the height of foot arch decreases (r = 0.47), these changes might also be affected by increasing BMI (r = -0.51) during growing up. Regarding the condition of preferred and non-preferred foot, no statistically significant difference was found out (p = 0.44). Based on the results we recommend compensatory exercises aiming to plantar flexors stretching to be included in artistic gymnasts` preparation.